Rise and fall of personnel (of) idad - Hevia-Garrido-Lecca, Julio (1995)
The individual interiority, then, opposite and / or complementary to a kind of social environmentalism, seems to involute or be disrupted by community flows lodged in the same subject, thus making it more permeable to the external. Gradually we witness a decentering of the self, a deportation of the self, an exile of the personality. Such a slide should not surprise us because it seems to constitute the reverse movement -or if you like, "the return of the repressed" of the succession given in the use of the word "person". We know that a Stoic, original reading exhausted such a significant in roles and staging, while the Christian vision, by emphasizing the aspect of substance, ended up centered on relationships: broad thematic and classically illustrated in the Father / Son / Holy Spirit triangulation. The most expensive concept -prosopon- overflowed initially by the support -hypostasis-, counterattack today with all the force of which it is capable.